ALISHER NAVO’I AND YAHYA BEY TASHLIJALI (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The article examines the great Uzbek poet Alisher Navo’i and his follower in Ottoman Turkish literature, poet, statesman and general Yahyabey. The life and creative path of Tashlijali are examined. In the article this two the artist social and literary in its activities similar directions is being examined.